Management theory and practice - Cole, Gerald A.; Kelly, Phil (Australia : Cengage Learning Asia Pte Ltd, 2011)
The aim of Management Theory and Practice 7ed is to provide an accessible introduction to the principal ideas and developments in management theory and practice.
Management theory -- Management in practice -- Functional management-marketing, production, personnel and financial.
Includes bibliographical references and index.